Floral biology and visitors of Montrichardia arborescens (L.) Schott (Araceae) in Caxiuanã National Forest, Amazon Region, Brazil - Junqueira, Camila Nonato; Muir, Jennifer; Pindar, Alana (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
The genus Montrichardia is widely distributed across the Brazilian Amazon, however very little is known about its floral biology and floral visitors. This study, carried out over four days in September 2011 in the Caxiuanã National Forest aimed to investigate aspects of floral biology such as inflorescence growth, reproductive function, fruit size and principal visitors of Montrichardia arborescens in eastern Amazonia. It was estimated that the inflorescences monitored over the four day period were open for between 48-72 hours. Open inflorescences emitted more heat during morning visits compared to evening visits. Floral visitor numbers were dramatically lower than those reported in other studies. Out of the 75 individuals of Montrichardia arborescens observed, only seven received visitors. Results also showed no significant difference in pollen viability across measured spadix sections. Lastly, the number of carpels per fruit showed no significant effect on fruit size and shape.